2017
DOI: 10.1111/gtc.12515
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Sarcocystis fayeri's actin‐depolymerizing factor as a toxin that causes diarrhea

Abstract: Raw horsemeat has the potential to induce food poisoning which often presents with diarrheal symptoms. A sample of horsemeat was found to be infected with Sarcocystis fayeri, and a 15-kDa protein isolated from the cysts of S. fayeri was found to clearly show its diarrhea-inducing activity. A nested polymerase chain reaction was used to clone the cDNA of the 15-kDa protein. The deduced amino acid sequence showed homology to actin-depolymerizing factor (ADF). A recombinant 15-kDa protein depolymerized prepolymer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…This toxin showed homology with the actin-depolymerizing factor from Toxoplasma gondii and Eimeria tenella . Irikura et al showed that a recombinant version of the same 15-kDa protein induced enterotoxicity in a rabbit ileal loop test (23). These findings showed that the 15-kDa protein from S. fayeri originating from horse meat was a diarrheal toxin functioning as a food poisoning agent in humans.…”
Section: Discussionmentioning
confidence: 99%
“…This toxin showed homology with the actin-depolymerizing factor from Toxoplasma gondii and Eimeria tenella . Irikura et al showed that a recombinant version of the same 15-kDa protein induced enterotoxicity in a rabbit ileal loop test (23). These findings showed that the 15-kDa protein from S. fayeri originating from horse meat was a diarrheal toxin functioning as a food poisoning agent in humans.…”
Section: Discussionmentioning
confidence: 99%
“…Sarcocystis spp. is one such novel intrinsic risk factor for food poisoning [10]. We previously reported the presence of at least four species of Sarcocystis spp.…”
mentioning
confidence: 99%
“…Irikura et al . also showed that the same 15-kDa protein of S. fayeri induced enterotoxicity in a rabbit ileal loop test using a recombinant 15-kDa protein [ 20 ]. Aoki et al .…”
mentioning
confidence: 99%